Blood Flow Velocity Waveforms of the Umbilical Artery in a Normal Population: Reference Values from 18 Weeks to 42 Weeks of Gestation - Bahlmann, F.; Fittschen, M.; Reinhard, I.; Wellek, S.; Puhl, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: The aim of the present study was to calculate new Doppler reference ranges for systolic, intensity-weighted mean, and end-diastolic blood flow velocities (Vmax, Vmean, Vmin) and fetal heart rate and impedance indices (PI, RI) of the umbilical artery by automatic waveform analysis. Materials and Methods: A cross-sectional prospective study of 1926 low-risk pregnancies was performed at 18 – 42 weeks of gestation. The measurements were carried out in the region of a free floating loop of cord. Reference ranges for the individual measuring parameters were constructed based on a growth function from a four-parameter class of monotonic continuous functions according to the smallest square principle. The intraobserver reliability was also assessed. Results: A significant increase in umbilical blood flow velocity was observed at 18 – 42 weeks of gestation (Vmax = 33.7 cm/sec to 65 cm/sec (p < 0.001), Vmean = 18.2 cm/sec to 38.7 cm/sec (p < 0.001) and Vmin = 8.2 to 31 cm/sec (p < 0.001). Reference curves for the pulsatility and the resistance index were associated with significant decreases with increasing gestational age (PI: 18 weeks: 1.3; 28 weeks: 1.1; 42 weeks: 0.8 and RI: 18 weeks: 0.7; 28 weeks: 0.6; 42 weeks: 0.5). The fetal heart rate decreased from 147 – 134 bpm. The intraobserver reliability was low, but of no clinical relevance. Conclusion: The reference ranges for blood flow velocities and resistance indices in the umbilical artery calculated by the authors serve as the basis for Doppler ultrasound antenatal examinations in a normal patient population and enable the early diagnosis of fetal risk.
Keywords: ultrasound color Doppler; fetus; umbilical artery; obstetrics; reference values